MATHEMATICAL AND COMPUTER MODELING OF FUNCTIONING LOGISTICS PROCESSES AND SYSTEMS - POTAPOVA, NADIIA; VOLONTYR, LUDMILA; ZELINSKA, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper substantiates the need of usage mathematical and computer modelling in data analysis in assessing with the functioning of logistic processes and systems. Based on the analysis of existing approaches, the peculiarities of using an integrated method of mathematical and computer modelling in order to effective set up and implement a process research experiment are revealed. The logistic system is formalized within the supply of material and technical resources by a centralized method of flow distribution and transfer of management influence from the highest level of the hierarchy to the lower levels such as branches or separate units. Formal identification of the logistic system of supply of material and technical resources is based on the separation of the main factors of the system and the limits of their impact.The main stages of modelling the functioning of logistics processes are specified, which is the basis for clarifying the algorithmic features of the computer experiment. It is stipulated that one of the main approaches to the study of these systems is modelling based on the use of methodological principles of queuing theory, which is based on modelling the flow characteristics of processes, orders and the discipline of their service. The procedure for determining the main characteristics of the system is focused on conducting computer simulations by setting up a computer experiment aimed at simulating the behaviour of the system and its evaluation. Probabilistic estimates of the queuing system are obtained under stationary operating conditions, in the established mode, which achieves limiting the impact of the conditions of the initial state. Emphasis is placed on combining simulation modelling as one of the approaches of computer modelling with elements of optimization solutions that can be obtained as an analytical solution to specific applications of logistics of varying complexity, in particular, inventory management.
Keywords: mathematical modelling; computer modelling; logistic system; logistic process; simulation model; experiment